Miao-Themed Souvenir Toys Design to Promote Tourism in Guizhou China - Jiangwei, Lu; Keai, Gregory Kiyai @ (South Asian Journal of Social Sciences and Humanities, 2024)
Purpose/Background: This study investigated the impact of Miao-themed souvenir toy design  on promoting tourism in Guizhou, China. The culturally diverse province has an opportunity  to leverage ethnic arts for tourism growth. Authentic representation of minority groups through  creative mediums can attract visitor interest.  Methods: A qualitative approach was used involving semi-structured interviews with Miao  artisans who design souvenirs. Detailed interviews examined artistic processes and cultural  representations in toys. Interview transcripts were analyzed using coding and thematic analysis. Findings: Interviews highlighted the cultural significance of toys for promoting both Miao  heritage and local tourism. Artisans play a key role in authentically conveying minority culture  through creative souvenirs. Culturally symbolic elements in toys resonate with tourists seeking  an immersive experience.  Conclusions: Findings demonstrate souvenir toy design as an avenue for boosting tourism  while preserving ethnic arts in Guizhou. However, time limitations prevented thorough  investigation of tourist preferences and trends influencing market success. Ongoing research is  critically needed on optimizing cultural designs and effective promotion for visitor appeal.
Keywords: Cultural heritage; Theme based souvenirs; Miao-themed toys; Tourism; Guizhou